2010
DOI: 10.1371/journal.pone.0011456
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Side Populations in HNSCC: Highly Invasive, Chemoresistant and Abnormal Wnt Signaling

Abstract: Side Population (SP) cells, a subset of Hoechst-low cells, are enriched with stem cells. Originally, SP cells were isolated from bone marrow but recently have been found in various solid tumors and cancer cell lines that are clonogenic in vitro and tumorigenic in vivo. In this study, SP cells from lymph node metastatic head and neck squamous cell carcinoma (HNSCC) cell lines were examined using flow cytometry and Hoechst 3342 efflux assay. We found that highly metastatic HNSCC cell lines M3a2 and M4e contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 31 publications
10
120
0
Order By: Relevance
“…Previous studies have revealed that the HNSCC cell lines, M3a2 and M4e, contain SP cells that are highly tumorigenic and are involved in chemoresistance and tumor invasion (24). In accordance with these findings, the present study identified that 2.7% of the metastatic HNSCC cells were SP cells.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have revealed that the HNSCC cell lines, M3a2 and M4e, contain SP cells that are highly tumorigenic and are involved in chemoresistance and tumor invasion (24). In accordance with these findings, the present study identified that 2.7% of the metastatic HNSCC cells were SP cells.…”
Section: Discussionsupporting
confidence: 90%
“…There has been conflicting data regarding the toxicity of Hoechst 33342 dye to live cells (Montanaro et al, 2004;Platet et al, 2007). Our result showed that SP cells have almost similar proliferation rate as Non-SP cells, coupled with previous work (Huang et al, 2009;Song et al, 2010), suggesting that cytotoxicity does not account for the cancer stem-like phenotype of SP cells.…”
Section: Discussionsupporting
confidence: 52%
“…The most frequently applied method for identifying CSCs is flow cytometry, which detects cells with the ability to excrete the vital DNA dye Hoechst 33342 (34)(35)(36)(37)(38). A distinctive small non-dyed population of cells, termed the side population (SP), has been detected in numerous tumors, and is highly tumorigenic (39)(40)(41)(42)(43)(44).…”
Section: Concept and Identification Of Cscsmentioning
confidence: 99%